Implementation of the Uninhabitable House Social Rehabilitation Program - Milli Milli; Nazaruddin Nazaruddin; Teuku Alfiady; Muklir Muklir (LPPM Universitas Malikussaleh, 2023)
Implementation of the Uninhabitable House Social Rehabilitation Program (RSRTLH). In its performance, several problems were found. First, there are large numbers of individuals without adequate housing. In addition, the distribution of beneficiaries of the RS-RTLH program has not been fully optimal, and the construction and renovation of houses have not been completed. This study aims to examine and describe the Uninhabitable House Rehabilitation Program implementation. In implementing the program delivered by Merilee S. Grindle, the tone of the program is appropriate, and the program objectives have been achieved. The research method uses a qualitative approach. The research results show that the program's implementation has not reached its target, indicating that the performance has not been by the observed impacts, and the level of change has not been running optimally as stated in the regulations that have been set. The inhibiting factors include the lack of involvement of related parties, budget constraints, and lack of community participation, so the program's implementation aims to be completed but has not yet obtained maximum results.